Confirmation of the Structures of Synthetic Derivatives of Migrastatin in the Light of Recently Disclosed Crystallographically Based Claims - Nagorny, Pavel (2010)
In the light of recently disclosed crystallographic studies on migrastatin ketone 2 complex with fascin, the structures of migrastatin ketone 2 and migrastatin ether 4 have been re-evaluated by NMR and X-Ray crystallographic techniques. The results of these studies established the correctness of the previously reported structural assignment and confirm that the “small molecule” co-crystallized in complex with fascin is not the migrastatin ketone, which was provided for the infusion experiment, but rather its stereoisomer.